1997
DOI: 10.1002/eji.1830270427
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of human epidermal Langerhans' cell B7‐1 and B7‐2 co‐stimulatory molecules in vivo by solar‐simulating irradiation

Abstract: Ultraviolet (UV) radiation impairs cutaneous immune functions and induces antigen-specific tolerance both locally at the irradiated skin site, as well as at distant skin sites and systemically. It has been postulated that in the local model, altered Langerhans' cells (LC) provide tolerogenic signals, and studies in vitro have indicated that UV radiation may down-regulate the expression of co-stimulatory molecules on the surface of these cells. To examine the effect of UV radiation on LC co-stimulatory molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Furthermore, we have found that UV radiation increases the T cell stimulatory capability of immature DC. These data are in accordance with studies that described the upregulation of CD80 and CD86 on human epidermal LC in vivo after simulated solar radiation (Laihia and Jansen, 1997). Interestingly, it has been described that p38‐mitogen‐activated protein kinase mediates the induction of both MHC‐II and CD86 and apoptosis on human‐monocyte derived DC after UVB induction (Nakagawa et al , 2004).…”
supporting
confidence: 93%
“…Furthermore, we have found that UV radiation increases the T cell stimulatory capability of immature DC. These data are in accordance with studies that described the upregulation of CD80 and CD86 on human epidermal LC in vivo after simulated solar radiation (Laihia and Jansen, 1997). Interestingly, it has been described that p38‐mitogen‐activated protein kinase mediates the induction of both MHC‐II and CD86 and apoptosis on human‐monocyte derived DC after UVB induction (Nakagawa et al , 2004).…”
supporting
confidence: 93%
“…This is the first report that demonstrates the activation of MoDC by UVB. Such activation has been observed in human LC irradiated in vivo or ex vivo (Laihia and Jansen, 1997;Nakagawa et al, 1999), but not when LC were firstly isolated and then irradiated in vitro (Weiss et al, 1995;Rattis et al, 1998). These discrepancies might have arisen for several reasons.…”
Section: Discussionmentioning
confidence: 85%
“…Using monocyte-derived dendritic cells (MoDC), it was demonstrated that activation of caspases 3, 8, and 9 was involved in the apoptotic processes (Nicolo et al, 2001). Some LC, however, showed maturation when they were irradiated with UVB in vivo or ex vivo (Laihia and Jansen, 1997;Nakagawa et al, 1999), but so far the mechanisms by which DC are activated by UVB have not been clear.…”
mentioning
confidence: 96%
“…Various treatments have been shown to induce or up‐regulate the expression of CD80 molecules. For example, stimulation of B cells with lipopolysaccharide, cross‐linking CD21/CD35 or CD19 on the surface of B cells 10 and solar stimulation of epidermal Langerhans cells have all been shown to increase the expression of CD80 11 . In previous studies, we reported that either partial inhibition of protein synthesis or X‐ray irradiation of the B lymphoma cells, A20‐2J, selectively enhances CD80 expression, and that this in turn results in the enhancement of their APC function 12,13 .…”
Section: Introductionmentioning
confidence: 99%